Resolving Radiant: Combining Spatially Resolved Longwave and Shortwave Measurements to Improve the Understanding of Radiant Heat Flux Reflections and Heterogeneity - Merchant, Coleman; Meggers, Forrest; Hou, Miaomiao; Aviv, Dorit; Schneider, Florian Arwed; Middel, Ariane (Frontiers in Sustainable Cities, 2022)
We introduce and demonstrate new measurement and modeling techniques to fully resolve the spatial variation in shortwave and longwave radiant heat transfer in the outdoor environment. We demonstrate for the first time a way to directly resolve the shortwave radiant heat transfer from terrestrial reflected and diffuse sky components along with the standard direct solar radiation using an adapted thermopile array and ray-tracing modeling techniques validated by 6-direction net radiometer. Radiant heat transfer is a major component of heat experienced in cities. It has significant spatial variability that is most easily noticed as one moves between shade and direct solar exposure. But even on a cloudy and warm day the invisible longwave infrared thermal radiation from warm surfaces makes up a larger fraction of heat experienced than that caused by convection with surrounding air. Under warm or hot climate conditions in cities, radiant heat transfer generally accounts for the majority of heat transfer to people. Both the shortwave (visible/solar) and the longwave (infrared/thermal) have significant spatial variation. We demonstrate sensor methods and data analysis techniques to resolve how these radiant fluxes can change the heat experienced by >1 kW · m -2 across small distances. The intense solar shortwave radiation is easily recognized outdoors, but longwave is often considered negligible . Longwave radiation from heat stored in urban surfaces is more insidious as it can cause changes invisible to the eye. We show how it changes heat experienced by >200 W · m -2. These variations are very common and also occur at the scale of a few meters.